Medial epicondylitis and cubital tunnel syndrome in the throwing athlete - Grana, W. (Clinics in Sports Medicine, 2001)
Medial epicondylitis and ulnar nerve problems are common in the throwing athlete, resulting from the tremendous valgus stress that occurs during the acceleration phase of pitching. They are too often ignored as a cause of medial pain in the throwing athlete in favor of the diagnosis of ulnar collateral ligament injury. The latter seems to be in vogue, and there is a virtual epidemic of reconstructive surgery to address this diagnosis. The question is whether more medial pain is caused by the former two diagnoses than the latter. We need to have a better understanding of the natural history and differential diagnosis of medial side pain, which, I hope, will come with time. Nonetheless, medial stress injuries occur in the throwing athlete, and can cause inflammation of the adjacent anterior capsule flexor pronator mass, the ulnar collateral ligament, and the ulnar nerve. This review highlights these problems, their anatomy, diagnosis, and management.